EU cohesion policy in the Czech Republic and Poland: Comparison of intervention areas among regions - Lenka Smékalová; Filip Kučera (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2022)
The cohesion policy of the European Union represents a significant part of its budget and delivers interventions across all regions of the EU. There is little consensus on its efficiency, and its links to fostering convergence on the regional level are uncertain. Nevertheless, regions were shown to benefit from policy interventions promoting their growth and development. The main objective of the policy is to reduce regional disparities that exist among lagging and other, more developed regions. Therefore, this paper focuses on the deliverance of the cohesion policy in Central and Eastern European countries, Poland and the Czech Republic. It explores the support of thematic interventions across its regions in the 2014-2020 period. Findings point out different thematic support of Polish regions according to their relative advancement. Lagging regions of Poland received more substantial support related to promoting the endogenous potential for development and increase in quality of human capital. In contrast, the Czech regions were treated comparably regardless of their development stages. This points to different approaches to implementing the cohesion policy in these countries.
Keywords: J18; R11; R58; 330; Cohesion policy; Regional development; European Structural and Investment Funds; Lagging regions; Czech Republic; Poland